Regional Logistics in Improving the Defense Economy in the Region - Arifin, Ahmad; Saputro, Guntur Eko; Haetami, Haetami (Graduate Program Magister Manajemen Pendidikan, 2022)
Covid-19 has had an impact not only on health but also on the resilience of the national economy. Learning from the history of war, if we have weapons without food reserves, it will be messy as well as increasing food security to anticipate the impact of disease outbreaks such as Covid-19 which could happen again in the future. The Ministry of Defense is serious about developing the Food Estate Program by reviewing several potential land locations for planting strategic commodities. The plan to develop the